The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/ep.13132
|View full text |Cite
|
Sign up to set email alerts
|

Resource management for green growth: Ensure environment sustainability agenda for mutual exclusive global gain

Abstract: The study aims to explore the dynamic relationships between Water‐Energy‐Food (WEF) resources, carbon‐fossil‐GHG emissions, and growth specific factors in the context of Pakistan by using an annual time series data from 1970 to 2016. The results of simultaneous Generalized Method of Moments (GMM) estimator show that industry value added largely influenced water's share in carbon emissions and fossil fuel combustion, while chemicals that used in manufacturing value added largely increases water's GHG footprints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…But in the context of the business world, the notion of ES belongs to a vast horizon ranging from environmental aspects ( Nidheesh and Kumar, 2019 ), social aspects ( Doğu and Aras, 2019 ), and economic aspects ( He et al, 2020 ) that is also regarded as triple bottom line (TBL) effect. There is a paradigm shift in business strategies related to environmental sustainability as the earlier version of ES was to control the rate of pollution that is now replaced with absolute ecological methods to be adopted by the businesses during their operations ( Nassani et al, 2019 ). As a result of all these activities, the notion of ES has registered itself as a critical factor for safe and healthy business activities ( Sandrin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…But in the context of the business world, the notion of ES belongs to a vast horizon ranging from environmental aspects ( Nidheesh and Kumar, 2019 ), social aspects ( Doğu and Aras, 2019 ), and economic aspects ( He et al, 2020 ) that is also regarded as triple bottom line (TBL) effect. There is a paradigm shift in business strategies related to environmental sustainability as the earlier version of ES was to control the rate of pollution that is now replaced with absolute ecological methods to be adopted by the businesses during their operations ( Nassani et al, 2019 ). As a result of all these activities, the notion of ES has registered itself as a critical factor for safe and healthy business activities ( Sandrin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Zaman et al (2017) confirmed the carbon fossil-methane EKC of sub-Saharan African (SSA) countries by analyzing the non-linear relationship between WEF resources and air pollutants. Nassani et al (2019) used the simultaneous generalized method of moments and investigated the relationships between WEF resources, carbon fossil-GHG emissions, and growth-specific factors to verify the EKC in Pakistan. Xu et al (2022) examined the link between economic growth and the WEF footprint by exploring the existence of the EKC in China's economic zones and regions.…”
Section: Environmental Kuznets Curve (Ekc) Hypothesis In Relation To ...mentioning
confidence: 99%
“…Every business, directly and indirectly, impacts the environment. (Nassani, et. al, 2019;Ogega, 2017).…”
Section: Introductionmentioning
confidence: 99%